AGRICULTURAL LAND AND FORESTRY ZONATION AS DISASTER MITIGATION EFFORTS TO DAS KAONISIK DISTRICT, DISTRICT TINGGIMONCONG GOWA - Zhiddiq, Sulaiman; Mannan, Abdul; Yusuf, Muhammad; Maddatuang, Maddatuang; Tabbu, Ansarullah; Yanti, Jeddah (Universitas Negeri Makassar, 2023)
Determination of land for the development of agricultural and forestry crops important to know as mitigation in the watershed Kaonisik Tinggimoncong Gowa district in South Sulawesi. Based on land suitability and productivity data supporting the use of land for agriculture and forestry crops on some land units. Land suitability classes determined by laboratory and field test results on a number of land characteristics that are matched to the criteria of the guidelines to grow plants with CSR/FAO staff (1983). Land mapping unit is the smallest unit that is used as the evaluation unit, obtained through remote sensing interpretation, analysis, topographical maps, geological maps, soil maps, land use, slope and soil, passed penampalan (overlay) to acquire land units map. The results showed that: 1) land suitability classes for agricultural crops; corresponding marginal (S3) 12 land units: 1450 ha (38.5%), does not match the current (N1) 1 unit area: 80.5 ha (2.2%), and not suitable permanent (N2) 11 land units: 2094 ha (59.3%). The limiting factor is the dominant medium roots (r), nutrients available (n), and terrain (s), while for forest plants: as marginal (S3) 8 units of land: 952 ha (24.9%), it is not appropriate at this time (N1) 6 unit of land: 644 ha (17.7%), not suitable permanent (N2) 10 land units: 2029 ha (57.4%). The limiting factor is the dominant medium roots (r). 2) Agihan sub-class of land suitability potential (S3rns) for the coffee plant in the village of Jonjo, Baliti, Majannang, Borong Bulo, Laloasa, Bangkitonro, Bontopanno, Gallang, with an area of 1450.5 ha Pattiro (38.5%), according to the plant sengon marginal (S3ns) Majannang village, Borong Bulo, Jonjo, Laloasa, Tonrokombang, and Manimbahoi with an area 952 ha (24.9%).